Axiological Potential of Philosophy of Education - Vakhovskyi, Leonid (Journal of Education Culture and Society, 2025)
Aim. The purpose of the study is to reveal the axiological potential of the philosophy of education and to identify ways towards an efficient impact on the value sphere of students’ personality.Methods. In order to achieve the goal, a set of methods was used: analysis, synthesis, induction, deduction, abstraction, comparative method, content analysis, systematisation, generalisation.Results. The concept of “value” is characterised, and an efficient strategy for introducing students to values, based on the principles of constructive axiology, is proposed.Conclusion. Realising the axiological function, the philosophy of education is called to: offer certain value ideas and principles as guidelines for education; theoretically justify approaches to enriching the value experience of students in the learning process. Value as the significance of objects and phenomena can act as a goal or ideal, as a norm that sets patterns and standards of behaviour. In conditions of rapid changes in the value picture of the world, the optimal approach is the approach that provides students' involvement in the value mastering of reality, active participation in the reassessment of values, their correction and construction.